PENGARUH SELF REGULATED LEARNING TERHADAP PRESTASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN EKONOMI - Rahmiyati, Anis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe purpose of this research was to know the influence of Self Regulated Learning to the students learning achievement class X on the economic subjects in SMAN 5 Pontianak. The method used in this research is assosiatif with the form of the research ekspos fakto, with a population of about 342 students so determined many sample by a formula slovin about 76 students. The data was collected by using direct communication technique (directive interview), indirect communication technique (self regulated learning questionnaire), and study documentary. The result of this research showed that there is the positive influence of the self regulated learning to the students learning achievement class X on the economic subject in SMAN 5 Pontianak. It is indicated by the number 2,757 which showed that there is an influence of the independent variable to dependent variable. When it is compared with T table on the significance level of 0,05 at 1,993. So it is greater than T table or 2,757 > 1,993, so Ha is accepted and Ho is rejected. The magnitude of the influence of self regulated learning on students learning achievement by 9.3% while the rest influenced by other factors are not described in this study.Â Keywords: Self Regulated Learning, Students Learning Achievement, Economic SubjectsÂ